Remotely pumped hybrid double-pass L-band optical amplifier utilizing chirped fiber Bragg - Jamaludin M.Z.; Abdullah F.; Al-Mansoori M.H.; Rawi N.I.M.; Idris S.M.; Haleem M.R. (2023)
This paper reported an investigation of remotely pumped double pass L-band amplifier with dispersion compensation technique. The proposed design used chirped fiber Bragg grating (CFBG) to reflect the amplified signal back into the active medium, compensate the effect of fiber dispersion and block the recycled forward amplified spontaneous emission (ASE) and the residual 1480 nm pump power. The characterization of the design was done experimentally. The gain is 37.5 dB and noise figure is 4 dB with best BER of 10-52 is achieved when the EDF is placed 150 km away from the transmitter and 48 km before the receiver terminal. © 2013 Elsevier GmbH.